Multiple syringoma. - Bonifazi, E.; Mazzotta, F.; Laforgia, N. (European Journal of Pediatric Dermatology, 2004)
Syringoma is an adenoma of the eccrine, intraepidermal sweat duct (2). Multiple syringoma is more frequent in females, starting gradually or rarely in an eruptive manner, and affecting, mainly in teenagers (4), the anterior surface of the neck and abdomen. Its asymptomatic, 2-3 mm in size, skin-colored or slightly pigmented papules should be differentiated from dermatitis (1), disseminated granuloma annulare, mastocytosis and Darier’s disease. The histological examination (3) shows small ducts with amorphous material, lined by 2 layers of flattened cells and characteristically provided by comma-shaped processes reminiscent of tadpoles. Prognosis. It does not regress and, when removed, can be followed by residual scar.